2021
DOI: 10.1038/s41598-021-93342-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure and radiobiological risk from thyroid radioiodine therapy in Saudi Arabia

Abstract: Worldwide, thyroid cancer accounts for some 10% of total cancer incidence, most markedly for females. Thyroid cancer radiotherapy, typically using 131I (T1/2 8.02 days; β− max energy 606 keV, branching ratio 89.9%), is widely adopted as an adjunct to surgery or to treat inoperable cancer and hyperthyroidism. With staff potentially receiving significant doses during source preparation and administration, radiation protection and safety assessment are required in ensuring practice complies with international gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Additionally, UNSCEAR, encouraged member states to provide data regarding patients and staff exposure due to the lack of reported values [1]. Limited studies were reported regarding occupational exposure during nuclear medicine examination in Saudi Arabia [10] [17]. The prior investigations revealed significant dosage variability due to variations in scanning methodology, perception methods, and NM technologist expertise.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, UNSCEAR, encouraged member states to provide data regarding patients and staff exposure due to the lack of reported values [1]. Limited studies were reported regarding occupational exposure during nuclear medicine examination in Saudi Arabia [10] [17]. The prior investigations revealed significant dosage variability due to variations in scanning methodology, perception methods, and NM technologist expertise.…”
Section: Introductionmentioning
confidence: 99%
“…Radioiodine results in a significant β-decay component. Contrariwise, for nuclear medical personnel, γ-emission represents the primary source of external exposure [ 29 ]. Radioiodine emitted radiation directly induces DNA damage or generates reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…Even with the use of the tungsten apron, the results might have been affected by basic radiation protective factors such as exposure time and distance from the child. Radiation exposure can be accumulated over time with prolonged exposure, and a greater distance from the radiation source can reduce radiation exposure 23 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The radiation doses of some caregivers of younger patients were > 5.0 mSv. On the other hand, in the case of 131 I therapy for thyroid diseases, the most famous nuclear medicine treatment, a medical worker’s annual occupational radiation exposure is < 2.2 mSv 25 , 26 . The occupational dose of up to 0.26 mSv per 131 I-MIBG therapy session in this study is considered to be higher than that of 131 I treatment.…”
Section: Discussionmentioning
confidence: 99%